Silver Nanoparticles Synthesized from Euphorbia tirucalli L. Latex Extract: Characterization and Antibacterial Activity Assessment (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2022)
Background:The fast production of silver nanoparticles utilizing plant latex extract from Euphorbia tirucalli L. is revealed in this study where the application of Euphorbia tirucalli latex extract in the green manufacture of Ag-NPS has been investigated as a reducing and stabilizing agent.Euphorbia tirucalli latex silver nanoparticles (Ag-NPs) were investigated using UV-VIS Spectroscopy and produced a surface plasmonic resonance peak at 400 nm. The size of Euphorbia tirucalli AgNPs was determined using a scanning electron microscope (SEM), which revealed nanoparticles ranging in size from ten to sixty nm, with average of 51.6 nm. The main significance of active functional groups in the reduction and stability of Euphorbia tirucalli AgNPs is revealed by Fourier-transform infrared spectroscopy (FTIR).The well diffusion assay was also used to detect antibacterial activity at four concentrations 100, 50, 25, and10 μg/ml against Gram positive bacteria Staphylococcus aureus and Enterococcus faecalis and gram negative bacteria Escherichia coli and Klebsiella pneumoniae as harmful microorganisms and the diameters of the prevention zone appeared varying according to the concentrations that were used. This research shows that employing a low-cost, environmentally acceptable extract as a major precursor in the manufacture of Ag nanoparticles is feasible and practicable, Finally, this supply of nanoparticles might be a very important industrial initiative in the search for innovative, safe, and cost-effective antibiotic alternatives.Materials and Methods:This study has been conducted in the advanced plant laboratory at the College of Science for women/ University of Babylon in cooperation with the laboratories of the Ministry of Industry and Minerals and AL-Ameen center for research and advance Biotechnology, AL-Najaf province to conduct some tests for the for the period from November 2020 to March 2021.Results:The current AgNP synthesis method, which uses latex extract as a reducing agent, completely eliminates the use of synthetic reducing agents. Latex is very good at producing very stable and biocompatible AgNPs, which might be useful in biomedical applicationsConclusion:The biosynthesis of Euphorbia tirucalli Ag-NPs was effectively accomplished in the current work using a green technique of manufacture that involved treating silver nitrate with latex extract of Euphorbia tirucalli solutions. The plant latex of Euphorbia tirucalli was shown to be a good stabilizing reducing agent for the production of AgNPs in this approach. The process used here is very basic, straightforward, low-cost, environmentally friendly, and a superior alternative to chemical synthesis. The resulting AgNPs are very stable and have good antibacterial activity.